"They will say you want to make their home die": A mixed methods study to assess modern family planning use in partnered South Sudanese refugee and host populations in Northern Uganda. - Neha S Singh; Pallavi Prabhakar; Agnes Ssali; Sylvia Namakula; Josephine Namatovu; Rogers Kapiti; Joram Kasiri; Sandra Mounier-Jack (Public Library of Science (PLoS), 2022)
The unmet need for family planning among conflict-affected populations is high globally, leaving girls and women vulnerable to unintended pregnancies and poor sexual and reproductive health outcomes. Ours is the first known mixed-methods study to assess the use of modern family planning (FP) methods amongst married or partnered South Sudanese refugee and host populations in Northern Uganda and to explore differences between them. We conducted a cross-sectional survey in July 2019 which included 1,533 partnered women of reproductive age (15-49 years) from host and South Sudanese refugee communities in Kiryandongo and Arua. Qualitative data were collected in October 2019-January 2020 via 34 focus group discussions and 129 key informant interviews with refugee and host populations, health workers, community and religious leaders, health workers, local authorities and humanitarian actors. Our study did not find large differences between South Sudanese refugee and host populations in regard to modern FP use, though refugees reported somewhat poorer FP knowledge, accessibility and utilisation compared to Ugandan women. Reported barriers to FP use relate to access, quality of services, health concerns and family/community opposition, all of which emphasise the importance of men's gendered roles in relationships, cultural and religious beliefs and lack of agency for most women to make their own decisions about reproductive health. Sexual and gender-based violence related to FP use was reported among both refugee and host populations. Additional barriers to FP use include lack of privacy at the public health facilities which reduces confidentiality, mistrust of health workers, and stockouts of FP commodities. Facilitating factors for FP use included: free government health services; the presence of well-trained health workers; and NGOs who give support to populations and conduct community outreaches. The findings of this study underscore the importance of developing and implementing tailored sexual and reproductive health information and services, especially for modern FP methods, in partnership with South Sudanese refugee and host populations in Northern Uganda.